Inalienable Land: Waqf-Based Land Tenure Security for Cooperative Urban Housing in Indonesia - Adam Ridho Muzakki; Zuhal Azzamul A'la (Bulletin of Indonesian Islamic Studies, 2025)
The provision of affordable community-driven cooperative housing models presents a promising alternative in Indonesia, optimizing land use by separating building costs from land ownership. However, the viability of this model is fundamentally undermined by land tenure insecurity. Residents who invest in the construction of their houses remain vulnerable, as the land held under a long-term lease can be sold, mortgaged, or alienated by the original landowner, risking their long-term security. This study conceptualizes Islamic legal framework of waqf (endowment) as a direct legal remedy to this specific vulnerability. This study employs a qualitative socio-legal analysis, collecting data through classical fiqh text that further analyzed for its feasibility within Indonesia’s contemporary Law No. 41 of 2004 concerning waqf, and used the Rujak Center for Urban Studies (RCUS) cooperative housing model as a case study. The results demonstrate that by synthesizing the principles of perpetuity and inalienability with the separation of corpus and usufruct, the risk from landowner default or third-party sale is mitigated. This study contributes a novel legal framework that reconceptualizes waqf not merely as a charitable act, but as an instrument for land tenure security.